Observational study on passive leg raising and the autonomic nervous system - Søren Søndergaard (Physiological Reports, 2022)
Abstract In the intensive care and perioperative setting, circulation is often supported by intravenous fluid preceded by prediction of fluid responsiveness during a passive leg raising (PLR) maneuver. An increase in stroke volume (SV) or cardiac output (CO) of 10%–15% indicates that the subject may increase the flow upon volume expansion. However, the semi‐recumbent position as an initial position in PLR likely reduces SV by gravitational displacement of central blood volume (CBV) to lower extremities, thereby accentuating volume responsiveness during leg raising in healthy people. Coincident with gravitational perturbations in hemodynamics, remedial changes occur in the autonomic nervous system (ANS), as expressed in spectral power in heart rate variability (HRV). This study aims to clarify these concomitant changes during PLR. A convenience number of healthy volunteers (N = 11) were recruited by advertisement in university departments. The subjects were exposed to the established PLR sequence and the heart rate (HR), mean arterial pressure (MAP), SV, and CO were sampled at 1 Hz, while electrocardiogram was recorded at 1000 Hz. Relative powers reflecting autonomic nervous system activity were assessed from spectral analysis of HRV. In response to PLR, SV increased (12.4% ± 8.7%, p < 0.0026), while HR (−7.6% ± 4.7%, p < 0.0009) and MAP (−7.6% ± 6.9%, p < 0.01) decreased, with no change in CO (4.1% ± 12.8%, ns). The HRV low‐frequency component was reduced (−34%; p < 0.0095), while the high‐frequency activity increased (78.5%; p < 0.0013), with a 63% decrease in the low/high frequency ratio (p < 0.0078). Thus, HRV indicated a reduced sympathetic index (semi‐recumbent 0.808 vs. PLR −0.177 a.u., p < 0.001) and an increased parasympathetic index (−0.141 to 0.996 a.u., p < 0.0001). Gravitational depletion and expansion of CBV during PLR were associated with a counterregulatory autonomic response. Healthy volunteers appeared volume responsive in terms of SV, but not CO. Responses to PLR are influenced by the ANS, and HRV analysis should be included in the assessment of the PLR test.